Abnormal immunoreactivity to serotonin in cerebellar purkinje cells after neonatal cocaine exposure - Summavielle, Teresa (2004)
Neonatal cocaine is known to affect the developing serotonergic system in many brain structures, including the cerebellum. Changes in the cerebellar Purkinje cells after drug exposure are well documented and result in impairment of movement and other cerebellar disorders such as ataxia. These cells have a major postnatal developmental pattern; therefore, neonatal exposure to cocaine is likely to affect them. In this work, male and female Wistar rats were injected with 15 mg of cocaine hydrochloride/kg body weight/day, subcutaneously, in two daily doses, from postnatal day 1 (PND1) to PND29. Controls were given 0.9% of saline. On PND14, PND21, and PND30, rats were transcardially perfused, and brains removed and cryoprotected. Coronal sections from the cerebellum were processed for immunocytochemistry of cells containing serotonin (5-hydroxytryptamine, or 5-HT). At the same postnatal age, rats from at least three different litters were sacrificed by decapitation, and brains were dissected for determination of 5-HT in the cerebellum by high-performance liquid chromatography with electrochemical detection. Upon the expected distribution of immunoreactivity to 5-HT, an abnormal immunoreactivity to 5-HT was observed in the Purkinje cells of six cocaineexposed animals, but not in control animals. Also, levels of cerebellar 5-HT in cocaine-exposed rats were significantly increased on PND21. These results, together with previously reported observations of altered patterns of motor behavior, indicate that neonatal cocaine exposure affects the serotonergic cerebellar system, altering the standard development of Purkinje cells and possibly compromising the motor function.